OZONE OBSERVATIONS AT SYOWA STATION FROM FEBRUARY 1987 TO JANUARY 1988 - カネト, ススム; ヤマモト, アキラ; オギハラ, ヒロユキ; スガワラ, ヒデトシ; ヤマノウチ, タカシ; KANETO, Susumu; YAMAMOTO, Akira; OGIHARA, Hiroyuki; SUGAWARA, Hidetoshi; YAMANOUCHI, Takashi (National Institute of Polar Research, 1990)
P(論文) Procedures and results of ozone observations at Syowa Station, East Antarctica, during the period from February 1987 to January 1988 are reported. The annual change of total ozone observed by a Dobson spectrophotometer shows remarkable depression in early October. The depression rate was about 50% of the normal value. The vertical distribution of ozone by chemical ozone sonde revealed that the total ozone depression results mainly from ozone decrease in the lower stratosphere. departmental bulletin paper